Superconductivity and Structural of the New Er358 Materials - Kruaehong, Thitipong; Sujinnapram, Supphadate; Sinwittarak, Somkid; Nilkamjon, Tunyanop; Ratreng, Sermsuk; Udomsamuthirun, Pongkaew (Science Essence Journal, 2023)
The Er358 superconductor was synthesized via the standard solid-state reaction method and demonstrated an average onset critical temperature of 95.48 K and an offset critical temperature of 89.70 K. Its crystal structure was classified into two groups: superconducting and non-superconducting compounds, possessing orthorhombic structures corresponding to the Pmmm and Pbnm space groups, respectively. The ratio of superconducting to non-superconducting compounds was 1:2, and their respective lattice parameters were a=3.8248 Å, b=3.8770 Å, c=31.666 Å, and a=7.1006 Å, b=12.139 Å, c=5.6418 Å. The samples exhibited smooth and dense surfaces, and their element distribution was analyzed via EDX mapping. The Cu2+/Cu3+ ratio was 0.0527, and the oxygen content deficiency was 0.300. The oxygen content was determined to be 17.7 using iodometric titration. Additionally, two endothermic peaks were observed in the heat reaction at 935°C and 1,050°C.